Comparison between PFN1 and SOD1 mutations in amyotrophic lateral sclerosis. (18th October 2022) - Corcia, Philippe; Lejeune, Pascal; Vourc'h, Patrick; Beltran, Stephane; Piegay, Anne‐Sophie; Blasco, Helene; Meininger, Vincent
Abstract: Background: The objective of this study was to characterize the prototypical phenotype of patients with amyotrophic lateral sclerosis (ALS) associated with PFN1 mutations in profilin 1 (PFN1) and to determine clinical indications to test for mutations in this gene. Material and methods: The phenotype of three relatives carrying the M114V PFN1 mutation are detailed here and are compared with those of patients with ALS linked to PFN1 previously reported in the literature. Results: In this pedigree and in the literature, the main clinical findings which best describe familial ALS linked to PFN1 might be the following characteristics: pedigrees over five cases, age of onset around 50 years, site of onset systematically lower limbs and the absence of cognitive impairment. Conclusion: First, the infrequent incidence of patients with ALS linked to PFN1 mutation supports the pursuit of a precise characterization of the phenotype linked to PFN1 mutations. Then, the numerous similarities between the phenotype amongst patients linked to SOD1 and PFN1 mutations and between histological features amongst both mice models prompts a review of the current ALS classifications, taking into consideration both phenotype and genotype.